2019
DOI: 10.4103/jispcd.jispcd_191_19
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative and quantitative evaluation of the efficiency of the application of foams with false xerostomia

Abstract: Aims: Xerostomia syndrome is a significant medical and social problem. It is manifested by objective and subjective symptoms of a “dry mouth” and a decrease in sialometry. The aim of the study was to determine the dental status of students of different nationalities, to identify xerostomia induced on a background of stress, and to assess the effectiveness of the use of moisturizing foams in alleviating xerostomia. Materials and Methods: A prospective cohort study survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
3
0
1
Order By: Relevance
“…The rate of remineralization of enamel is determined by many factors, including the remineralizing effect of saliva, the amount of which, even in healthy people, may decrease under the stress. [ 23 ]…”
Section: Discussionmentioning
confidence: 99%
“…The rate of remineralization of enamel is determined by many factors, including the remineralizing effect of saliva, the amount of which, even in healthy people, may decrease under the stress. [ 23 ]…”
Section: Discussionmentioning
confidence: 99%
“…Oral care foams and sprays may be considered an alternative to mouthwashes in cases where the use of the latter is inconvenient, as only few mouthwashes are available in portable size packages. It was found that oral foams can increase salivation [62]. To the best of our knowledge, there have been no previous studies regarding the neutralizing effect of oral foams or sprays with different compositions.…”
Section: Introductionmentioning
confidence: 94%
“…Causes of this subjective symptom include changes in the composition of saliva [16], mouth breathing, atypical oral and facial symptoms, burning mouth syndrome, oral dysesthesia, and mental, psychological, and psychiatric disorders. In over half of false xerostomia cases, a 50% decrease in the amount of oral fluids was observed [18].…”
Section: Xerostomiamentioning
confidence: 99%